2013
DOI: 10.1177/1088357613504992
|View full text |Cite
|
Sign up to set email alerts
|

Formative Evaluation of an ABA Outreach Training Program for Parents of Children With Autism in Remote Areas

Abstract: Families in rural or remote areas have limited access to evidence-based intervention for their children with autism. Using web-based training and telemedicine technology, the current study investigated the feasibility of training seven parents to implement Applied Behavior Analysis (ABA) strategies with their children with autism. In this exploratory formative evaluation, parents increased their knowledge of ABA strategies and concepts by an average of 39 percentage points, and improved their implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(143 citation statements)
references
References 64 publications
7
117
1
2
Order By: Relevance
“…25 Because telehealth can provide research-based ABA treatment to any family with access to the Internet, barriers to providing access to ABA can be reduced, especially for rural and underserved families. There is a rapidly growing literature on the use of telehealth to deliver a range of ASD interventions, [26][27][28][29][30] and future issues regarding the delivery of ABA services via telehealth will need to focus on when to provide services and at what intensity to deliver them in relation to other interventions. These timing and dose issues warrant careful study, as will issues such as the effects of ABA treatment on caregiver stress and parenting and the best ways to ensure generalization of children's and parents' newly learned skills.…”
Section: Resultsmentioning
confidence: 99%
“…25 Because telehealth can provide research-based ABA treatment to any family with access to the Internet, barriers to providing access to ABA can be reduced, especially for rural and underserved families. There is a rapidly growing literature on the use of telehealth to deliver a range of ASD interventions, [26][27][28][29][30] and future issues regarding the delivery of ABA services via telehealth will need to focus on when to provide services and at what intensity to deliver them in relation to other interventions. These timing and dose issues warrant careful study, as will issues such as the effects of ABA treatment on caregiver stress and parenting and the best ways to ensure generalization of children's and parents' newly learned skills.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it was beyond the scope of the review to consider interventions that did not include additional support from a trainer (e.g. those based solely on self-directed learning such as Jang et al 2012), or interventions relating to more broad behavioral methodology rather than defined procedures (e.g., Heitzman-Powell et al 2014;Vismara et al 2009;Vismara et al 2013;Vismara et al 2012); therefore, the utility of telehealth in these contexts cannot be inferred from this review. In addition, due to the nature of systematic review methodology, some relevant articles may not be included if they were not identified as part of the search strategy and it was not possible to include gray literature such as unpublished manuscripts, dissertations, or book chapters.…”
Section: Limitations and Areas For Further Studymentioning
confidence: 99%
“…Although some authors have applied telehealth methodology to more broad training (see, for example, Heitzman-Powell et al 2014;Reese et al 2015;Vismara et al 2009Vismara et al , 2013Vismara et al , 2012Xie et al 2013), an analysis of the factors related to the effectiveness of telehealth for different types of support and with different behavioral targets is warranted. Finally, the motivations and context for adopting telehealth support in ABA services must be considered.…”
Section: Broader Considerations Relating To Telehealthmentioning
confidence: 99%
“…Educators who received support reported positive outcomes and stakeholder data were positively correlated with gains in school-wide outcomes. Heitzman-Powell, Buzhardt, Rusinko, and Miller (2014) used formative evaluation to measure knowledge of behavioral strategies and concepts taught in a web-based training program for parents of children with autism as well as intervention feasibility and costs vs. benefits. Findings were used to improve the program design.…”
mentioning
confidence: 99%